THE ROLE OF LEADERSHIP AND BUSINESS STRATEGY TO ENHANCE BUSINESS PERFORMANCE OF DIGITAL CREATIVE INDUTRY IN JAKARTA - A. Victoria Rahajeng Widyarsih (Sosiohumaniora, 2023)
This study aims to examine the influence of leadership and business strategy on the business performance of the digital creative industry. The unit of analysis in this study is a company engaged in the digital creative industry in DKI Jakarta, with the unit of observation being company management. Data collection will be carried out in 2023. The sampling method is purposive sampling and involves 50 respondents from digital creative companies in DKI Jakarta. The statistical analysis tool for processing the data is SmartPLS. This research was conducted to examine the influence of leadership and business strategy on business performance. The research was conducted at the analysis unit of digital creative industry companies in DKI Jakarta. The results of hypothesis testing show that leadership and business strategy have a significant influence on business performance. Business strategy has a more dominant influence on business performance. The managerial implication of this research is that companies need to apply the right business strategy by prioritizing a speed-based strategy and by initiating mutually beneficial partnerships with competitors, in addition to continuing to carry out various other business strategies. In addition, digital creative industry management must also strengthen leadership so that it can direct employees toward improving business performance.